Islamic Law and Customary Law in Contemporary Legal Pluralism in Indonesia: Tension and Constraints - RR Dewi Anggraeni (Universitas Islam Negeri Jakarta, 2023)
Legal pluralism poses a challenging issue in the application of law in society. Indonesia, as a pluralistic country with diverse ethnicities, customs, and religions, faces conflicts between legal systems. This study addressed the conflicts between Islamic law, state law, and customary law regarding inheritance within the kinship system of Indonesian society. Data were collected from court decisions and legal scholars' opinions, which were then analyzed using the theories of legal pluralism, receptio in complexu, and receptio a contrario. The study found that legal conflicts arise among customary laws within the matrilineal, patrilineal, and parental kinship systems, particularly in inheritance matters. Legal conflicts occur when faced with Islamic law, which resonates with religious practices, and state law, which applies to all citizens. Based on several court decisions, the inheritance distribution resulting from differences in legal systems, especially within the customary kinship system, is disregarded in favor of state and Islamic law. This study implies a shift in the inheritance distribution system, which is no longer purely based on the kinship system of indigenous communities. Keywords: legal pluralism; Islamic law; state law; inheritance distribution AbstrakPluralisme hukum menjadi isu yang menantang dalam penerapan hukum di suatu masyarakat. Indonesia sebagai negara plural yang memiliki perbedaan suku, adat, dan agama menghadapi pertentangan antar sistem hukum. Studi ini membahas pertentangan hukum Islam, hukum negara dan hukum adat dalam soal pembagian waris dalam sistem kekerabatan masyarakat Indonesia. Data dikumpulkan dari putusan-putusan pengadilan dan pendapat para sarjana hukum yang kemudian dianalisis dengan teori pluralisme hukum, teori receptio in complexu dan teori receptio a contrario. Studi ini menemukan bahwa terjadi konflik hukum antar hukum adat dalam sistem kekerabatan matrilineal, patrilineal, dan parental, khususnya dalam pembagian waris. Konflik hukum juga terjadi ketika dihadapkan pada hukum Islam yang menjadi afinitas masyarakat dalam beragama dan hukum negara yang menjadi hukum bagi semua warga negara. Berdasarkan sejumlah putusan pengadilan, pembagian waris akibat perbedaan sistem hukum, khususnya dalam sistem kekerabatan dalam hukum adat dikesampingkan dari hukum negara dan hukum Islam. Studi ini berimplikasi pada bergesernya sistem pembagian waris yang tidak lagi murni berdasarkan sistem kekerabatan masyarakat adat. Kata Kunci: pluralisme hukum; hukum Islam; hukum negara; pembagian waris